(untitled) (Geo-Eco-Marina, 2023)
This paper presents the fluctuation of the calcareous nannoplankton species Emiliania huxleyi and Braarudosphaera bigelowii identified in four cores sampled from the NW Black Sea, at various water depths, between 160.9 and 1.031 m. Unit 1 (Coccolith Mud) and 3 (Lacustrine Lutite) are present in all studied cores, the former showing a variable thickness. Unit 2 (Sapropel Mud) was not observed in the shallowest studied cores, i.e., above 200 m water depth. At the deepest levels of the studied cores, a red-brownish succession, composed of clays and muds, was identified. Calcareous nannoplankton assemblages in situ are present only in the youngest Holocene units 1 and 2, being composed of Emiliania huxleyi and Braarudosphaera bigelowii. These two calcareous nannoplankton species, very abundant especially in Unit 1, show a negative correlation in their abundance pattern.